Inorganic photovoltaics – Planar and nanostructured devices. (September 2016) - Ramanujam, Jeyakumar; Verma, Amit; González-Díaz, B.; Guerrero-Lemus, R.; del Cañizo, Carlos; García-Tabarés, Elisa; Rey-Stolle, Ignacio; Granek, Filip; Korte, Lars; Tucci, Mario; Rath, Jatin; Singh, Udai P.; et al.
Abstract: Since its invention in the 1950s, semiconductor solar cell technology has evolved in great leaps and bounds. Solar power is now being considered as a serious leading contender for replacing fossil fuel based power generation. This article reviews the evolution and current state, and potential areas of near future research focus, of leading inorganic materials based solar cells, including bulk crystalline, amorphous thin-films, and nanomaterials based solar cells. Bulk crystalline silicon solar cells continue to dominate the solar power market, and continued efforts at device fabrication improvements, and device topology advancements are discussed. III–V compound semiconductor materials on c-Si for solar power generation are also reviewed. Developments in thin-film based solar cells are reviewed, with a focus on amorphous silicon, copper zinc tin sulfide, cadmium telluride, as well as nanostructured cadmium telluride. Recent developments in the use of nano-materials for solar power generation, including silicon and gallium arsenide nanowires, are also reviewed.